2022
DOI: 10.3390/en15217823
|View full text |Cite
|
Sign up to set email alerts
|

Model Antiseptic Control Scheme to Torque Ripple Mitigation for DC-DC Converter-Based BLDC Motor Drives

Abstract: Although brushless direct current motor (BLDCM) drives are becoming more popular in industrial and commercial applications, there are still significant difficulties and unresolved research issues that must be addressed. In BLDCM drives, commutation current ripple (CCR) and diode freewheeling during non-commutation zone (NCZ) are the major challenges. To overcome these limitations, this paper proposes a novel PWM-Model Antiseptic Control (PWM-MAC) technique to alleviate the freewheeling of the diode. The propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It was observed that the PWM-ON switching offered 58.9% ripples, whereas the proposed method offered only 24.7% of the torque ripples. The PWM-ON-PWM method was able to reduce the torque ripples by 34.2%, which is a lesser result than that mentioned in [23]. The effectiveness of the proposed strategy was illustrated by simulation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It was observed that the PWM-ON switching offered 58.9% ripples, whereas the proposed method offered only 24.7% of the torque ripples. The PWM-ON-PWM method was able to reduce the torque ripples by 34.2%, which is a lesser result than that mentioned in [23]. The effectiveness of the proposed strategy was illustrated by simulation.…”
Section: Discussionmentioning
confidence: 85%
“…In [22], torque ripple was effectively reduced at about 28%, where copper losses and torque pulsations were somewhat reduced by using the dq-Transformation. In [23], torque ripples due to the diode free-wheeling of the inactive phase were considered, and were suppressed by nearly 32.5% using the PWM-Model Antiseptic Control Technique.…”
Section: Introductionmentioning
confidence: 99%
“…2023. 7-19: 6-11 Introduction DC motors have wide popularity because they are very versatile in industrial (Kumar, Surya, Tabrez, Afida, & Molla Shahadat, 2022), domestic (Khan, et al, 2021), and laboratory (Said, et al, 2022) mechanical applications. In many industries, DC motors are used as elements that perform essential tasks within their processes.…”
Section: Modelado Difuso Control Motor CDmentioning
confidence: 99%
“…A novel model predictive control-based PWM has been developed to address diode freewheeling and commutation current ripple in BLDC motors in [8]. Through simulations, the technique has demonstrated significant reductions by 32.5% for the torque ripples which is considered a big step towards performance enhancement compared to the conventional PWM.…”
Section: Introductionmentioning
confidence: 99%